Vulnerability of the elderly with traumatic cervical injury - Yanmara Betharte Sotomayor; Delvis Serra Reyes (Medisur)
Foundation: older adults suffer falls that produce traumatic complications, among which is spinal cord trauma with a high rate of disability and mortality. Objective: to set out the prognostic factors that affect the elderly with traumatic cervical spinal injury. Methods: a cross-sectional study was carried out with 42 geriatric patients diagnosed with spinal cord trauma treated in Camagüey, from 2019 to 2022. The research consisted of a stage for the collection of demographic data, the type of accident, the level of injury, medical complications, the therapy used and another where the statistical processing was carried out where the mortality variable was considered as dependent. Results: a predominance of patients between 60 and 74 years of age was observed. The statistical analysis on the probabilities of dying showed that in a traumatic cervical event, patients with assisted mechanical ventilation, medical complications, injury severity level (ASIA A or B) who suffered a traffic accident had a higher risk of dying than those who were not in these groups. The level of social dependence of the group was between moderate and severe. Conclusions: population aging requires the development of specialized therapies, where the morphophysiological characteristics of this group are taken into account, which will allow better functional recovery and an adequate quality of life.